THE POWER OF WOMENS SOLIDARITY: A STUDY OF ALICE WALKER THE COLOR PURPLE - Williams, Betsy (IJRDO - Journal of Social Science and Humanities Research, 2017)
Alice Walker is one of the most famous and cherished writers, and this is largely due to the novel 'The Color Purple'. The novel won her considerable praise and criticism for its controversial themes. Alice Walker was a precious child, but after being blinded in one eye at age eight in an accident with a BB gun by one of her brothers. By the time they reached a doctor a week later, she had become permanently blind in that eye. When a layer of scar tissue formed over her wounded eye, Alice became self- conscious and painfully shy. Stared at and sometimes taunted, she felt like an outcast and turned for solace to reading and to writing poetry. But later she realized that her traumatic injury had some value: It allowed her to begin "really to see people and things, really to notice relationships and to learn to be patient enough to care about how they turned out". Walker has always given credit to her mother for encouraging her to make something of herself, her father and brothers failed to give her a positive male role model.